A High‐Performance Bidirectional Direct Current TENG by Triboelectrification of Two Dielectrics and Local Corona Discharge. Issue 25 (22nd May 2022) - Shan, Chuncai; He, Wencong; Wu, Huiyuan; Fu, Shaoke; Tang, Qian; Wang, Zhao; Du, Yan; Wang, Jian; Guo, Hengyu; Hu, Chenguo
Abstract: Triboelectric nanogenerators (TENGs) are regarded as a promising technology to convert ambient low‐frequency mechanical energy into electricity for distributed power supply. Although TENGs based on triboelectrification (TE) of metal–dielectric and air breakdown have the advantage of direct current (DC) output, the unidirectional and single‐channel output mode limits their energy utilization efficiency. Here, a bidirectional and double‐channel (BDC‐TENG) based on TE of dielectric–dielectric and local corona discharge is proposed. Different from traditional DC‐TENGs, the TE process of the BDC‐TENG occurs in two dielectrics, and the double‐channel output is generated from simultaneous discharge between each dielectric and its adjacent electrode fixed on both sides of the slider. The BDC‐TENG shows unique characteristics, in that the current direction is tunable by adjusting the slider movement direction and electronegativity difference of two dielectric materials, and the average output power density is up to 3 W m –2 which is 14 times higher than that of traditional DC‐TENGs. This work provides a feasible strategy to boost the output performance of DC‐TENGs. Abstract : Here, a bidirectional and double‐channel triboelectric nanogenerator (BDC‐TENG) based on triboelectrification of the dielectric‐dielectric and local corona discharge is proposed. The BDC‐TENG shows unique characteristics, in that the current direction is tunable by adjusting the slider movement direction and electronegativity difference of the two dielectric materials, and the average output power density is up to 3 W m ‐2 .